Angle of arrival estimation of on-body channels - Kamarudin, Muhammad Ramlee (2007)
Angle of arrival (AoA) estimation has been performed on five on-body channels, namely belt-to-chest, belt-to-wrist, belt-to-ankle, belt-to-head and belt-to-back. The transmitter was always placed on the belt whilst the receiver was located on the points mentioned above. A quarter wavelength monopole and a switched beam array were used, respectively, as a transmitter and a receiver. The results show that the main propagation paths of the transmitted signal are limited to a limited interval of the AoA range. Such AoA estimates for on-body propagation channels can be used for designing better fixed beam and pattern diversity antennas.